PEMERIKSAAN KESEHATAN GRATIS KEPADA MASYARAKAT DESA TATAH LAYAP, KECAMATAN TATAH MAKMUR, KABUPATEN BANJAR - Muhammad Ma'ruf; shafran ilahi, fitrah; Prihandiwati, Erna; Susanto, Yugo; Ariani, Novia; Musiam, Siska; Wahyuni, Amaliyah; Rizki Febrianti, Dwi; Puteri Amalia, Senya; Ayu Lestari, Desy (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Regular health check-ups play a vital role in detecting health disorders early to prevent and treat illnesses appropriately. The free health check-up program in Tatah Layap Village, Tatah Makmur Subdistrict, Banjar Regency, aims to raise community awareness about the importance of promotive and preventive measures in maintaining health. This activity includes health education through communication, information, and education (CIE) approaches, as well as direct health examinations for the community. The program was attended by 85 participants who gained valuable information and understanding of the importance of regular health check-ups. The examination results served as a guide for participants to monitor and maintain their health conditions. This program is expected to enhance community awareness about the significance of routine health check-ups as a preventive measure to reduce the risk of future illnesses